KOMUNIKASI ANTARPERSONAL KOMUNITAS TRANSPUAN DI MOJOKERTO - Dwi Magfiroh, Rizky; A.H.Lailin, Moch. Ichdah; Ningsih, Masnia (Universitas Islam Majapahit, Indonesia, 2021)
From time to time the issue of sexuality is never out of debate. Especially with the rise of cases about sexuality.Sexuality, in the past, was a taboo subject to be discussed or disclosed in public, one of which was a trans woman phenomenon. Transwomen haveshow an identity and try to interact with the community by forming a transwomen community in Mojokerto. Transwoman inMojokerto has its own way of showing its behavior to the community, various perceptions from the community make them closeself. The purpose of this study was to find out how the interpersonal communication of the trans woman community in Mojokerto is. Qualitative research methodsselected using a phenomenological approach. Data collection techniques used interview and observation techniques. Data analysis processusing data collection, data reduction, data presentation and drawing conclusions. From the results of this study it can be concluded that the behavior ofTranswomen communication in Mojokerto can be seen from the way they interact with the community and their behavior. How to interact withtransgender society is more closed. Their behavior can be seen in many aspects such as how to dress, style or clothing, gestures.